Intergenerational Transmission of Cultural Knowledge and Craftsmanship: An Ethnopedagogical Point of View - Yulian Purnama; I Wayan Artika (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study is grounded in the importance of recognizing local wisdom-based educational practices that continue to exist amid the forces of modernization and globalization. The research problem focuses on how ethnopedagogical practices are implemented by the stone carving community in Muntilan, Magelang Regency, as an alternative educational model capable of transmitting knowledge across generations in a sustainable manner. The study employs a qualitative approach using a case study method to explore community-based learning processes through family apprenticeship, direct observation, and practical experience that integrates technical skills, aesthetic sensitivity, spiritual values, and Javanese philosophy. The findings reveal a distinctive learning ecology that emphasizes the internalization of tacit knowledge, character formation, and the close relationship between learning processes and socio-cultural life. The community also demonstrates adaptive resilience through its ability to adopt innovation without abandoning core cultural principles. The conclusion confirms that ethnopedagogical practices among the Muntilan stone carvers represent an effective and relevant contextual education model to support the preservation of intangible cultural heritage while addressing the challenges of modern education. The novelty of this study lies in the integration of ethnopedagogy with traditional craft practices as a holistic and sustainable non-formal education system, as well as its contribution to the discourse on decolonizing education and strengthening culturally based vocational education policies.